Model Peningkatan Kinerja Petani Kopi Arabika di Kabupaten Kerinci - Kristanto, Raja Bastian; Fitriaty, Fitriaty; Lubis, Tona Aurora (Universitas Batanghari Jambi, 2024)
This research aims to determine the direct and indirect influence of Supply Chain Management (SCM) on Performance Improvement through Government Policy. This research is quantitative research using a survey research design. The sample in this study consisted of 70 coffee farmers in Kerinci district taken using the Purposive Sampling Technique. The data collection instrument is a questionnaire with a Likert Scale format consisting of five alternative answers. Data from filling out the questionnaire will be analyzed using the Partial Least Square (PLS) technique. The research results show that the SCM has a significant influence on Performance Improvement and Government Policy, the Government Policy variable has a significant influence on Performance Improvement and the Government Policy variable is able to mediate the SCM on Performance Improvement.